Disclosure of oral pre-exposure prophylaxis use for HIV prevention among women enrolled in a contraceptive study: qualitative findings from Durban, South Africa - Ivana Beesham; Mags Beksinska; Cecilia Milford; Cecilia Milford; Leila E. Mansoor (Frontiers in Global Women's Health)
BackgroundDisclosure of oral pre-exposure prophylaxis (PrEP) use for HIV prevention may improve adherence to PrEP; however, disclosure can be challenging and may result in stigma. Here, we describe disclosure of PrEP use among young women enrolled in a contraceptive study.MethodsIn this qualitative study, we conducted semi-structured, in-depth, face-to-face interviews with 13 women aged 18–25 years who initiated oral PrEP for HIV prevention during the Evidence for Contraceptive Options and HIV Outcomes (ECHO) Trial. Interviews were conducted in 2021 with women from Durban, South Africa. In this analysis, we explore women's experiences of PrEP disclosure including whether they disclosed PrEP use, who they disclosed to and the reaction to disclosure, and the impact of disclosure on PrEP use. Interviews were conducted in English, audio-recorded and transcribed. Data were analysed thematically.ResultsAll women disclosed oral PrEP use to at least one individual, with some women disclosing to multiple individuals including family, friends, partners and community members. Few women did not disclose oral PrEP use to their partner due to anticipating a negative reaction from the partner, feeling that the partner would assume the woman has HIV and is taking antiretroviral therapy and fear that the partner would associate PrEP use with the woman having other partners. Reactions to oral PrEP disclosure were generally supportive or neutral, however, few women reported negative reactions that included distrust in the efficacy of PrEP to prevent HIV, discouraging the woman from using oral PrEP because of the assumption that PrEP is HIV treatment, and concern about the woman having oral PrEP side effects. Negative reactions to disclosure generally did not impact on oral PrEP use. Supportive disclosures sometimes resulted in reminders for oral PrEP dosing.ConclusionOur findings indicate that women are willing to disclose their PrEP use to at least one other person when supported. These study findings may contribute to future PrEP counselling guidelines and strategies.